Sarcopenia index based on serum creatinine and cystatin C is associated with mortality in middle-aged and older adults in Chinese: A retrospective cohort study from the China Health and Retirement Longitudinal Study - Wu, Yang; Wang, Hai; Tong, Yingmu; Zhang, Xing; Long, Yunxiang; Li, Qinglin; Ren, Jie; Liu, Chang (Frontiers in Public Health, 2023)
Abstract Background: The sarcopenia index (SI, serum creatinine/serum cystatin C × 100) is recommended for predicting sarcopenia. There were several studies showing that lower SI is associated with poorer outcomes in the older adults. However, the cohorts studied in these researches were mainly patients hospitalized. The aim of this study was to evaluate the correlation between SI and all-cause mortality among middle-aged and older adults from the China Health and Retirement Longitudinal Study (CHARLS). Materials and methods: A total of 8,328 participants meeting the criteria were enrolled in this study from CHARLS between 2011 and 2012. SI was calculated as (serum creatinine (mg/dL)/cystatin C (mg/L)) × 100. Mann-Whitney U test and Fisher's exact test were used to assess balance in baseline characteristics. Kaplan-Meier, log-rang analysis, univariate and multivariate Cox hazard ratio regression models were used to compare the mortality between different SI levels. The dose relationship between sarcopenia index and all-cause mortality was further assessed by the cubic spline functions and smooth curve fitting. Results: After adjustment for potential covariates, we found SI was significantly correlated with all-cause mortality [Hazard Ratio (HR)=0.983, 95% confidence interval (CI) 0.977 to 0.988, P < 0.001]. Similarly, as SI was used as a categorical variable according to quartiles, higher SI was associated with lower mortality [Hazard Ratio (HR) = 0.44, 95% CI 0.34 to 0.57, P < 0.001] after adjustment for confounders. Conclusions: Lower sarcopenia index was associated with higher mortality among middle-aged and older adults in China.